Synthesis and Characterization of Methyl Amino Polystyrene as Resin Material of Chromatography - Herman Herman; Anni Anggraeni; Abdul Mutalib; Husein H. Bahti (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Ion-exchange chromatography has been widely used in various separation process and purification. Commercial ion-exchange resin mostly uses polystyrene as stationer phase. This study reviewed the synthesis of cation-exchange resin with polystyrene as starting material. Polystyrene must be activated in order to make one of aromatic carbon chains being able to be binding with acetamide n-hidroxymethyl electrophilic. Polystyrene activation was conducted through two stages, i.e. (1) the formation of amidomethyl polystyrene (AMDP), and followed with (2) elimination of acyl group. The activation of polystyrene generated white methylamino polystyrene (MAP) resin, of which its characterization used spectrophotometry UV, Fourier Transform-Infrared (FTIR), and density of MAP resin confirmed by pycnometer. The results showed that the characterization of FTIR and spectrophotometer UV for AMP exhibited forming amino propyl group at 3374.52 cm-1 with ?max 230 nm due to N–H bond; and the average of density of AMP resin sample was 1.7158 g/mL.